Vulnerabilidad y areas criticas a deslizamientos en la microcuenca del rio Talgua, Honduras - Reyes, W.=700 1 Jimenez O, F.; Faustino M, J.; Velasquez, F.
(Es, En)
Ilus., 11 ref.
Keywords: DESLIZAMIENTO DE TIERRAS; DESASTRES; RIESGO; HONDURAS; MICROCUENCAS; VULNERABILIDAD